PENGARUH BURNOUT SYNDROME TERHADAP PROSES ASUHAN KEPERAWATAN (STUDI PADA PERAWAT RUMAH SAKIT MEDIKA UTAMA BLITAR) - Cipta Perdana Wijaya (REVITALISASI : Jurnal Ilmu Manajemen, 2019)
This research was to examine the effect of burnout syndrome on the nursing procces. Burnout syndrome was a complex criteria which not only on the physiological and psychological fatigue but also dominant conjunction with a decreasing in physical performance, their fatigue feeling, decreasing motivation and work productivity. Continously Physical activity and concentration can be measured with the physiological changes in the body that decreasing time reaction and the psychological changes that their feelings of fatigue, especially for Indonesian workers. Fatigue can be caused by several factors, among others shift rotation, individual factors (health/disease, gender, age, education, workload, life style and nutritional status) and physical environment factors (noise, light, temperature and heat stress, vibration and ventilation). The research used quantitative with descritive design, enrolled from July to August 2016. This study sample comprised of 26 respondents which included in inclution criteria. The independent variable was burnout syndrome whereas the dependent variables were nursing procces. The data had been proccesed in simple regression test with significant level of p < 0,05. The result of this research was the majority of the nurse, burnout syndrome occured in the emotional exhaustion dimention. Burnout Syndrome could affect the process of nursing care to nurses in the Medika Utama Hospital Blitar. Burnout Syndrome affects the nursing care procces in the data collection/assessment procces, nursing diagnosis process, implementation of nursing procces and nursing documentation process. Based on the reseach results, we could conclude that burnout syndrome had a significant effect in nursing procces. To avoid the significant effect of burnout syndrome, the nurses of Medika Utama Hospital better organize their physical force in order to be ready to work at any time. Used the free time and days off for rest. There should be a policy for the regulation of shift work by not allowed a nurse to work more shifts (morning shift continued to afternoon shift) by exchanging office hours.